2015
DOI: 10.4103/0972-124x.153488
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of dental professionals toward tobacco use

Abstract: Background:The habit of tobacco consumption has plagued all nations from time immemorial. While tobacco use is decreasing in many developed countries, it is increasing in developing countries like India. Health care professionals have a key role to play to motivate and advise tobacco users to quit.Aim:The aim was to assess the attitudes and practice of dental professionals in Mumbai and Navi Mumbai toward tobacco cessation and the potential barriers faced.Materials and Methods:Questionnaire-based survey was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This finding is consistent with studies in Kuwait, Kenya and Finland that reported a negative attitude towards patient counselling about smoking among healthcare professionals who smoke compared to those who are nonsmokers (24)(25)(26). This provides insight into the fact that dentists hold strong beliefs that they serve as a role model to their patients (11,12).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is consistent with studies in Kuwait, Kenya and Finland that reported a negative attitude towards patient counselling about smoking among healthcare professionals who smoke compared to those who are nonsmokers (24)(25)(26). This provides insight into the fact that dentists hold strong beliefs that they serve as a role model to their patients (11,12).…”
Section: Discussionsupporting
confidence: 88%
“…Most dentists believe it to be their responsibility to help their patients with tobacco cessation or to prevent tobacco use. A study in India showed that 98.7% of dentists felt that they were responsible for providing tobacco cessation advice, and 94.7% reported that they were confident in providing tobacco cessation advice to their patients (7)(8)(9)(10)(11)(12). A study among dentists in Kelantan, Malaysia showed that 72.7% were confident in giving such counselling.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is considered a threat to oral and systemic public health [4,35]. Dentists and oral health care professionals play a major role promoting the cessation of smoking among their patients [36]. In the present investigation, the prevalence of smoking was 5.36% in preclinical and 8.62% in clinical students.…”
Section: Discussionmentioning
confidence: 46%
“…Smoking is a worldwide hazard to systemic and oral public health [ 3 , 40 ]. Oral healthcare professionals play a key role in encouraging their patients and society to cease smoking [ 41 ]. Egypt is one of 15 countries globally with a distressing burden of smoking-associated health problems, having an estimated 20.3% smoking prevalence among the general population [ 42 ].…”
Section: Discussionmentioning
confidence: 99%